Effects of Using Storyline Method on English Reading Comprehension Skills of 12th Grade Students - Liengtrakulchai, Wannisa; Prasansaph, Soranabordin (Ratchaphruek Journal, 2020)
The research objectives were to study 1) English reading comprehension skills after using Storyline Method of 12th grade students and 2) the students’ opinions toward English Reading Comprehension using Storyline Method. The population was 226 students of Khoksamrong Wittaya School. The sample was 24 students of Khoksamrong Wittaya School in the 1st semester of the academic year 2019. The sample was selected by simple random sampling. The students studied 4 lessons using Storyline Method to develop English reading comprehension skills. The instruments in the study consisted of 4 Storyline lesson plans, English reading comprehension skills test, a questionnaire about students’ opinions toward Storyline method on English Reading Comprehension and a survey form of students’ need on reading texts. The data were analyzed by mean ( ), standard deviation (S.D.), and t-test (Dependent). The findings of the study revealed that 1) students’ English reading comprehension skills after using Storyline Method were significantly higher than before using Storyline Method at the significant level of .05, and 2) the students’ opinions toward Storyline Method on English reading comprehension skills were at the high level.